Counselling for burnout in Norwegian doctors: one year cohort study - Rø, Karin E Isaksson (BMJ Publishing Group Ltd., 2008)
Objective To investigate levels and predictors of change in dimensions of burnout after an intervention for stressed doctors. Design Cohort study followed by self reported assessment at one year. Setting Norwegian resource centre. Participants 227 doctors participating in counselling intervention, 2003-5. Interventions Counselling (lasting one day (individual) or one week (group based)) aimed at motivating reflection on and acknowledgement of the doctors’ situation and personal needs. Main outcome measures Levels of burnout (Maslach burnout inventory) and predictors of reduction in emotional exhaustion investigated by linear regression. Results 185 doctors (81%, 88 men, 97 women) completed one year follow-up. The mean level of emotional exhaustion (scale 1-5) was significantly reduced from 3.00 (SD 0.94) to 2.53 (SD 0.76) (t=6.76, P<0.001), similar to the level found in a representative sample of 390 Norwegian doctors. Participants had reduced their working hours by 1.6 hours/week (SD 11.4). There was a considerable reduction in the proportion of doctors on full time sick leave, from 35% (63/182) at baseline to 6% (10/182) at follow-up and a parallel increase in the proportion who had undergone psychotherapy, from 20% (36/182) to 53% (97/182). In the whole cohort, reduction in emotional exhaustion was independently associated with reduced number of work hours/week (β=0.17, P=0.03), adjusted for sex, age, and personality dimensions. Among men “satisfaction with the intervention” (β=0.25, P=0.04) independently predicted reduction in emotional exhaustion. Conclusions A short term counselling intervention could contribute to reduction in emotional exhaustion in doctors. This was associated with reduced working hours for the whole cohort and, in men, was predicted by satisfaction with the intervention.